Organic Solar Cells: Three‐Dimensional Nanostructured Indium‐Tin‐Oxide Electrodes for Enhanced Performance of Bulk Heterojunction Organic Solar Cells (Adv. Energy Mater. 7/2014). Issue 7 (May 2014) - Kwon, Hyunah; Ham, Juyoung; Kim, Dong Yeong; Oh, Seung Jae; Lee, Subin; Oh, Sang Ho; Schubert, E. Fred; Lim, Kyung‐Geun; Lee, Tae‐Woo; Kim, Sungjun; Lee, Jong‐Lam; Kim, Jong Kyu
<x xml:space="preserve">Abstract</x> A three‐dimensional indium tin oxide (ITO) nanohelix array is used as a multifunctional photoelectrode for bulk heterojunction organic solar cells. In article number 1301566, Jong‐Lam Lee, Jong Kyu Kim, and co‐workers demonstrate that the unique structural and optical properties of the ITO nanohelix array enable simultaneous improvements in light harvesting and charge transport efficiencies, resulting in enhanced power conversion efficiency. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>